Development of Curriculum Management Models in the Addiction Science Study Program - Erna Setiyaningrum; Ismet Basuki; Sri Setyowati (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
Drug abuse among students is a worrying problem that can threaten the survival of nation. This study carried tesearch design for the development of the Four D model is a model to develop learning devices. This method and model were chosen to develop addiction science education management that required to conduct feasibility, product validity, and trial. The development model based on curriculum management development referred to 4D development model, and referred to two quality requirements, namely valid and effective. This research objectives are to develop of curriculum management model for addiction science study program at IOHC INA Mojokerto, East Jawa, Indonesia. The quality of the Addiction Education Management Curriculum based on the final results had met the criteria